2013
DOI: 10.1016/j.ahj.2013.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in chronic heart failure: An international pooled analysis

Abstract: Iron deficiency is common in patients with chronic HF, relates to disease severity, and is a strong and independent predictor of outcome. In this study, ID appears to have greater predictive power than anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
580
13
58

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 594 publications
(688 citation statements)
references
References 38 publications
37
580
13
58
Order By: Relevance
“…It does not appear to correlate with function capacity or LV stiffness 235. A pooled analysis in a mixed population of HFpEF and HFrEF patients found that iron deficiency without anemia portends a worse prognosis than anemia without iron deficiency 236. From a therapeutic standpoint treatment with erythropoietin alpha does not improve functional capacity or reduce LV mass in elderly HFpEF patients 237…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…It does not appear to correlate with function capacity or LV stiffness 235. A pooled analysis in a mixed population of HFpEF and HFrEF patients found that iron deficiency without anemia portends a worse prognosis than anemia without iron deficiency 236. From a therapeutic standpoint treatment with erythropoietin alpha does not improve functional capacity or reduce LV mass in elderly HFpEF patients 237…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…Prevalence rates of iron deficiency (ID) in Southeast Asian HF patients also exceed those in European patients, averaging 61% and peaking at 80% in patients of Indian ethnicity 3. Regardless of ethnicity, geographical location, and anaemia status, concurrent HF and ID has consistently been associated with poor outcomes such as reduced exercise capacity, reduced quality of life (QoL), and elevated risks of HF hospitalization and mortality 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of patients with CHF are iron deficient 12, 13, 14. Iron deficiency (ID) is defined as a ferritin level <100 μg/L or ferritin 100–299 μg/L with a transferrin saturation <20% 12.…”
Section: Introductionmentioning
confidence: 99%